Reformasi Hukum Pidana dalam Menghadapi Kejahatan Transnasional: Studi Perbandingan Indonesia dan Uni Eropa - Alexandra, Sallie; Rosdiana (Universitas Sains dan Teknologi Komputer, 2025)
Transnational crime has become an increasingly complex challenge due to globalization and technological advancements, requiring effective legal frameworks to address cross-border offenses. Indonesia's criminal law system faces significant weaknesses compared to the European Union (EU), particularly in extradition mechanisms, international cooperation, and regulatory harmonization. This study aims to analyze the effectiveness of Indonesia's criminal law in combating transnational crime by comparing it with the legal framework of the EU. A comparative legal study approach was used, incorporating qualitative analysis of legal regulations, case studies, and interviews with legal practitioners and law enforcement officers. The study examined key aspects such as extradition policies, law enforcement capacity, and cross-border collaboration. The findings indicate that Indonesia’s extradition success rate remains at 45%, significantly lower than the EU's 85%, which benefits from the European Arrest Warrant (EAW). Furthermore, the average case resolution time in Indonesia is approximately 24 months, whereas in the EU, it is around 6 months due to more streamlined procedures. The research also highlights the need for Indonesia to strengthen its law enforcement agencies, as the limited use of digital forensic tools and artificial intelligence-based crime detection hinders investigative efficiency. This study contributes to the discourse on transnational crime by emphasizing the necessity for Indonesia to implement legal reforms that align with global standards, enhance technological adoption in law enforcement, and establish more robust international partnerships. Strengthening these areas will improve Indonesia’s ability to effectively address transnational crime and enhance its integration into the global legal framework.